Neuroprotective effect and preparation methods of berberine - Sunhe, Yi-Xuan; Zhang, Yue-Hui; Fu, Rui-Jia; Xu, Ding-Qiao; Tang, Yu-Ping (Frontiers in Pharmacology, 2024)
Berberine (BBR) is a natural alkaloid, which has played an important role in the field of medicine since its discovery in the late 19th century. However, the low availability of BBR in vivo prevents its full effect. In recent years, a large number of studies confirmed that BBR has a protective effect on the nervous system through various functions, yet the issue of the inability to systematically understand the protection of BBR on the nervous system remains a gap that needs to be addressed. Many existing literature introductions about berberine in neurodegenerative diseases, but the role of berberine in the nervous system goes far beyond these. Different from these literatures, this review is divided into three parts: preparation method, mechanism, and therapeutic effect. Various dosage forms of BBR and their preparation methods are added, in order to provide a reasonable choice of BBR, and help to solve the problem of low bioavailability in treatment. More importantly, we more comprehensively summarize the mechanism of BBR to protect the nervous system, in addition to the treatment of neurodegenerative diseases (anti-oxidative stress, anti-neuroinflammation, regulation of apoptosis), two extra mechanisms of berberine for the protection of the nervous system were also introduced: bidirectional regulation of autophagy and promote angiogenesis. Also, we have clarified the precise mechanism by which BBR has a therapeutic effect not only on neurodegenerative illnesses but also on multiple sclerosis, gliomas, epilepsy, and other neurological conditions. To sum up, we hope that these can evoke more efforts to comprehensively utilize of BBR nervous system, and to promote the application of BBR in nervous system protection.